A brief review of fatigue design criteria on offshore wind turbine support structures - Paulo Mendes; José A.F.O. Correia; Abílio M.P. De Jesus; Bianca Ávila; Hermes Carvalho; Filippo Berto (Fracture and Structural Integrity)
In this paper, a brief review of the main fatigue design criteria and some advanced fatigue approaches applied to offshore structures (e.g. offshore wind turbines) are presented. It is extremely important to understand the fatigue phenomenon and how it affects structures since offshore structures are constantly submitted to cyclic loading and corrosive attacks that aggravate the problem. All the influencing factors and approaches used during the design phase are also discussed.